The results of immunohistochemical study of signaling pathways’ markers of proliferation in uterine leiomyoma in women using hormonal contraception. - Finkova, E.P. (Морфологія / Morphologia / Morfologìâ, 2021)
Objective. To elucidate the influence of various components of hormonal contraception in women with uterine leiomyoma (UL) on the key molecular and cellular mechanisms of its proliferation. Methods. Antigen Ki-67, estrogen receptors (ER) and progesterone receptors (PR) were determined by immunohistochemical methods in 230 samples of UL preparations obtained during myomectomy. Depending on the composition of the components of hormonal contraceptives that women used for 12 months before the operation, 8 study groups were created: Group I - control, without the use of any hormonal contraception; Group II - the use of COCs containing 20 μg of ethinylestradiol and 0.075 mg of gestaden; Group III - COCs (30 μg ethinylestradiol and 0.075 mg gestaden) Group IV - COCs (30 μg ethinylestradiol and 0.15 mg desogestrel) Group V - COCs (30 μg ethinyl estradiol and 0.15 mg levonorgestrel) Group VI - COCs (30 μg ethinyl estradiol and 2 mg dienogest) Group VII - COCs (30 μg ethinylestradiol and 3 mg drospirenone) Group VIII - (intrauterine levonorgestrel releasing system (IUD-LNG). Results. In UL samples from group I, an increase of Ki-67 positive cells in 3.4 times was observed (3.1 ± 0.03%; p <0.04) in comparison with intact myometrium (IM) (0.9 ± 0.06%), which is evidence of a higher cell proliferation in the UL, a 3.1-fold increase in the H-index of ER expression - 39.4 ± 4.3 (p <0.05) versus 12.9 ± 1.6 in the group with IM I and in 2.6 times of PR expression - 21.1 ± 1.7 (p <0.05) compared to IM - 8.2 ± 1.4, which may indicate a greater sensitivity of UL to sex hormones and their promoter role in UL proliferation. Expression of Ki-67 in UL samples in women taking COCs, which included dienogest (1.8 ± 0.03%, p <0.05) - group VI and desogestrel (1.9 ± 0.03%, p <0.05) - group IV, was, 42.0% and 38.8% respectively, what ois less than in group I UL, which can be regarded as the cytoprotective effect of the progestogen component of COC on the mitotic activity of UL cells. A positive trend in the expression of Ki-67 persisted when women used COCs containing gestodene (2.1 ± 0.02%; p <0.05) - group III and levonorgestrel (2.2 ± 0.04%, p <0.05) - group V, in which the expression of Ki-67 was shown by a smaller number of PM cells, respectively, by 32.3% and 25.8% than in group I PM, and also to a lesser extent - in group VIII (COC with droperidone), where the mean value of Ki-67 expression in LM samples was 2.6 ± 0.02% and was 16.9% less than in LM group I. An increase in the dose of ethinyl estradiol in COCs from 20 μg (group II) to 30 μg (group III) did not significantly affect the expression of Ki-67, therefore, the content of estrogens in modern low-dose COCs does not contribute to an increase in proliferation in the LM, and the non-contraceptive antiproliferative effect is associated exclusively with biological and the pharmacological properties of individual gestagens in the composition of COCs. It was proved that the studied COCs did not significantly affect the expression of ER and PGR. There was no significant difference in the expression of the Ki-67 marker (2.9 ± 0.04%, p <0.05) in UL cells in women using LNG-IUD for contraception, compared with group I. Conclusion. The results of the study have shown that when choosing a drug for hormonal contraception in women with UL, preference should be given to combined hormonal drugs that contain progestogens with the most pronounced antiproliferative properties (dienogest, desogestrel and levonorgestrel).